SMARCA4 loss irrelevant for ARID1A mutated ovarian clear cell carcinoma: A case report - Samantha Kay Wagner; Ashley S. Moon; Brooke E. Howitt; Malte Renz (Elsevier, 2023)
Clear cell carcinomas are rare and relatively chemo-insensitive ovarian cancers with a characteristic molecular pathogenesis. Alterations in ARID1A, a component of the multiprotein chromatin remodeling complex SWI/SNF, are likely early events in the development of ovarian clear cancers arising from atypical endometriosis. Insight into additional driver events and particularly mutations in the same chromatin remodeling complex is limited. Isolated loss of SMARCA4, encoding the ATPase of the SWI/SNF complex, characterizes other aggressive gynecologic cancers including small cell carcinomas of the ovary hypercalcemic type (SCCOHT), undifferentiated endometrial carcinomas (UDEC), and uterine sarcomas (SDUS). The ovarian clear cell carcinoma of a 48-year-old showed in the initial surgical specimen a subclonal loss of SMARCA4 in addition to an ARID1A mutation, i.e., two alterations in the SWI/SNF heterochromatin remodeling complex. We anticipated that the SMARCA4 loss would worsen the disease course in analogy to SCCOHT, UDEC, and SDUS. However, the disease did not accelerate. Instead, the recurrent disease showed restored SMARCA4 expression while retaining the ARID1A mutation. Combinatorial redundancy, diversity and sequence in the SWI/SNF complex assembly as well as DNA- and tissue-specificity may explain the observed irrelevance of SMARCA4 loss in the presented ARID1A mutated ovarian clear cell carcinoma.